2023
DOI: 10.1186/s12944-023-01964-3
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic and visceral fat deposition in aging, obesity, and idiopathic pulmonary fibrosis: an interconnected role

Xiaoyun Cheng,
Shuhan Jiang,
Boyu Pan
et al.

Abstract: Idiopathic pulmonary fibrosis (IPF) is considered an age-related disease. Age-related changes, along with other factors such as obesity, hormonal imbalances, and various metabolic disorders, lead to ectopic fat deposition (EFD). This accumulation of fat outside of its normal storage sites is associated with detrimental effects such as lipotoxicity, oxidative stress, inflammation, and insulin resistance. This narrative review provides an overview of the connection between ectopic and visceral fat deposition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 150 publications
0
1
0
Order By: Relevance
“…Correlation analysis revealed a significant negative correlation between T2DM remission and IPFD. A rodent model study reported a strong association between IPFD and a high-fat/high-glucose diet, which not only abnormally increased plasma glucose levels but also predisposed the body to adverse effects, such as oxidative stress, inflammation, and islet cell apoptosis[ 19 , 20 ]. Excessive intra-abdominal fat deposition has also been suggested to increase the risk of cardiovascular disease and diabetic nephropathy in T2DM[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis revealed a significant negative correlation between T2DM remission and IPFD. A rodent model study reported a strong association between IPFD and a high-fat/high-glucose diet, which not only abnormally increased plasma glucose levels but also predisposed the body to adverse effects, such as oxidative stress, inflammation, and islet cell apoptosis[ 19 , 20 ]. Excessive intra-abdominal fat deposition has also been suggested to increase the risk of cardiovascular disease and diabetic nephropathy in T2DM[ 21 ].…”
Section: Discussionmentioning
confidence: 99%